The matter of rhyme : verse-music and the ring of ideas - Norris, Christopher, 1947- (Sussex Academic Press, 2018)
The poetry of ideas, a long neglected genre, has now found a vigorous and resourceful champion in Christopher Norris. Hitherto best known as philosopher and literary theorist, he has treated that genre to a full-scale modern revival of singular scope and ambition. His poems combine intellectual agility with a verse-music both keen-eared and frequently haunting. This latest collection sees Norris at the top of his bent as lyric poet, poet-philosopher, verse-essayist, political satirist, social commentator, and skilful re-worker of traditional verse-forms to suit contemporary contexts and concerns. It exhibits all the wit and erudition that readers will have come to expect, along with a marked broadening of purview and heightened stylistic virtuosity. These poems engage with topics ranging from the personal (though never private-confessional) to the deeply enquiring (though never abstruse) and the forcefully political (though never excluding issues that transcend the narrowly partisan). Above all they make the case for viewing rhyme, meter, and prosodic structure as intrinsically a part of verse-practice and a source of everything that is most distinctive and valuable in poetry.
Keywords: English poetry -- History.; Poésie anglaise -- Histoire.; POETRY -- English, Irish, Scottish, Welsh.; English poetry; poetry.; History; Poetry.; Poésie.